Bone Marrow Microenvironment in Multiple Myeloma Progression. (3rd October 2012) - Manier, S.; Sacco, A.; Leleu, X.; Ghobrial, I. M.; Roccaro, A. M.
Abstract : Substantial advances have been made in understanding the biology of multiple myeloma (MM) through the study of the bone marrow (BM) microenvironment. Indeed, the BM niche appears to play an important role in differentiation, migration, proliferation, survival, and drug resistance of the malignant plasma cells. The BM niche is composed of a cellular compartment (stromal cells, osteoblasts, osteoclasts, endothelial cells, and immune cells) and a noncellular compartment including the extracellular matrix (ECM) and the liquid milieu (cytokines, growth factors, and chemokines). In this paper we discuss how the interaction between the malignant plasma cell and the BM microenvironment allowed myeloma progression through cell homing and the new concept of premetastatic niche.